2010
DOI: 10.1186/1476-511x-9-121
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue: is it affected by intermittent hypoxia?

Abstract: BackgroundIntermittent hypoxia (IH), a model of sleep apnea, produces weight loss in animals. We hypothesized that changes in brown adipose tissue (BAT) function are involved in such phenomenon. We investigated the effect of IH, during 35 days, on body weight, brown adipose tissue wet weight (BATww) and total protein concentration (TPC) of BAT.MethodsWe exposed Balb/c mice to 35 days of IH (n = 12) or sham intermittent hypoxia (SIH; n = 12), alternating 30 seconds of progressive hypoxia to a nadir of 6%, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In morbidly obese patients undergoing bariatric surgery, ARON-WISNEWSKY et al [33] found no association between intermittent hypoxia and macrophage accumulation or adipocyte size in omental or subcutaneous fat; tissue PO 2 was not measured. As BAT is concerned, a trend towards decreased body weight and BAT in rats exposed to isocapnic intermittent hypoxia for 3 weeks has been reported [34]. No study to date has examined the role of chronic intermittent hypoxia on the transition from white to brown adipocytes, a topic of great interest in the current obesity literature.…”
Section: Osa and Type 2 Diabetes: An Independent Relationship?mentioning
confidence: 99%
“…In morbidly obese patients undergoing bariatric surgery, ARON-WISNEWSKY et al [33] found no association between intermittent hypoxia and macrophage accumulation or adipocyte size in omental or subcutaneous fat; tissue PO 2 was not measured. As BAT is concerned, a trend towards decreased body weight and BAT in rats exposed to isocapnic intermittent hypoxia for 3 weeks has been reported [34]. No study to date has examined the role of chronic intermittent hypoxia on the transition from white to brown adipocytes, a topic of great interest in the current obesity literature.…”
Section: Osa and Type 2 Diabetes: An Independent Relationship?mentioning
confidence: 99%
“…The inhibitory effects of hypoxia on the intensity of coldinduced BAT activity include a lower afferent blood flow to BAT [48], reduced sympathetic nerve activity [49], desensitized response to norepinephrine (a potent BAT activating agent [50,51]) [52], and can eventually lead to a reduction in BAT mass during prolonged exposure to hypoxia [53,54]. In addition, hypoxia results in the inhibition of shivering upon exposure to low Ta compared to normoxic controls in mice, dogs, and man [42].…”
Section: The Effect Of Hypoxia-induced Anapyrexia On Thermoregulatorymentioning
confidence: 99%
“…Mice were kept six each in cages measuring 30 x 19 x 13 cm, at an average room temperature of 22.4º ± 0.6° C and controlled humidity, on a standard 12/12 hour light-dark cycle (lights on at 0700, lights out at 1900). This method was described previously (18,19). All procedures were performed in accordance with the Guide for the Care and Use of Laboratory Animals (20) and were approved by the institutional animal care committee, Hospital de Clínicas de Porto Alegre (CEUA/HCPA #2009/09300).…”
Section: Animalsmentioning
confidence: 99%
“…The intermittent hypoxia procedure has been described previously in adult male mice (18,19), a mixture of 90% N 2 and 10% CO 2 was released into the cages over a period of 30 seconds, gradually reducing the oxy gen fraction to 7 ± 1% and increasing the CO 2 fraction to approximately 5 ± 1%; fans were then operated for 30 seconds so as to introduce room air into the cage. Overall, 480 such cycles of hypoxianormoxia occurred per day.…”
Section: Intermittent Hypoxia Systemmentioning
confidence: 99%
See 1 more Smart Citation